Design and Implementation of Z-Source Inverter by Simple Boost Control Technique for Laboratory Scale Micro-Hydro Power Plant Application - Ariefianto, Rizki Mendung; Aprilianto, Rizky Ajie; Suryoatmojo, Heri; Suwito, Suwito (Jurnal Teknik Elektro, 2021)
In a power plant such as micro-hydropower (MHP), an induction generator (IG) is usually employed to produce electrical power. Therefore, an inverter is needed to deliver it with high efficiency. Z-source inverter (ZSI) has been introduced as a topology with many advantages over conventional inverters. This research aims to investigate the performance of ZSI based simple boost control (SBC) in laboratory-scale MHP systems using a rewinding induction generator. This research has been conducted both from simulations and experiments. Based on the result, the waveform characteristic and value of ZSI are close to the desired design. A shoot-through duty ratio of 17% can reach 60 Vrms output voltage, and this condition has a conversion ratio of about 2.05 times. Also, SBC can significantly reduce the Total Harmonic Distortion (THD). ZSI efficiency has a value of 84.78% at 50% of rating load 100 W and an average value of 80%. Compared to the previous study, the proposed design has more economical with the same component for the higher rating power. Moreover, it has a smoother and entire output waveform of the voltage.